Analisis Hubungan Antara Iklim Komunikasi Organisasi Dengan Kinerja Karyawan di Cv. Sindunata Kartasura - Waikambari, Isroniah Joko, Agus Triyono, S.Sos, M.Si (2017)
Climate good communication within the organization needed for the work process that runs in the enterprise require coordination with each other. The purpose of this study was to describe the relationship between organizational communication climate with employee performance. This study uses a quantitative method with statistical analysis. The population in this study were all employees of CV. Sindunata Kartasura totaling 178 employees. The number of samples taken in this study were 36 employees. Instead of using random sampling techniques. Data were analyzed using correlation analysis. The results showed that: there is a positive correlation between communication climate within the organization with employee performance CV. Sindunata. Analiss correlation of the results obtained by the value of having rxy> rtabel namely 0.728> 0.329, p = 0.000 accepted at significance level of 5%. This shows that the climate is more conducive communication within the organization, the higher the performance of employees. Conversely the less favorable climate of communication within the organization, the lower the performance of the employee. Organizational communication climate conducive corporate environment characterized by conditions that are safe, comfortable, the relationship between leadership and employees takes place in harmony, employee relations with each other in harmony.